Autologous adipocyte graft in endoscopic treatment of vesico-renal reflux in children: a preliminary study - Isabelle Lacreuse; Raphael Moog; Vanessa Kadoch; Michel Fischbach; Marile-laurence Poli Merol; François Becmeur (MDPI AG, 2009)
No bulking agent is ideal for endoscopically treating vesico-renal reflux in children. Many teams have tried to find a safe and efficient material, ideally an autologous material. We describe here a protocol for the use of autologous viable fat in the treatment of primary vesico-renal reflux in children aged from 3 to 15 years. Fat harvesting was done from the medial side of the thigh by manual aspiration. Samples were centrifuged to purify the graft from blood and lipid. Lastly fat was injected beneath the pathologic ureter by a conventional endoscopic technique. A voiding cystourethrography (VCUG) closed the procedure. Follow-up included renal ultrasonography the day after surgery, and one and three months later. A VCUG was performed systematically at three months and, in cases of acute pyelonephritis, during the survey. Sixty-four children with 94 refluxing units were treated by autologous fat injection with a follow-up from 6 to 40 months. At the end of the procedure, we systematically obtained a very good increase in height of the pathologic meatus and VCUG was normal in all cases. None presented with an obstruction during the follow-up period. Two children presented with an acute pyelonephritis before the third month. At three months, VCUG was not realized in 14 cases (22%) because the parents refused the procedure. One of those children presented with an acute pyelonephritis five months after endoscopic treatment. VCUG was normal for 17 of 50 children (34%), and showed a real improvement for 19 other children (38%). Three children had a surgical reimplantation because of the persistence of an unchanged high-grade vesico-renal reflux; histological examination found viable adipocytes on sections of the distal pathologic ureter. Clinically, 11 children (17%) presented with an acute pyelonephritis after treatment at a mean follow-up time of 10 months. These preliminary findings led us to modify the technique in order to improve our results. Our first concern is feasibility and safety of this technique, regardless of the use of other synthetic bulking agents the innocuousness of which is uncertain.